1988
DOI: 10.1111/j.1445-5994.1988.tb02236.x
|View full text |Cite
|
Sign up to set email alerts
|

Articular Manifestations of Acromegaly

Abstract: Forty-five patients with acromegaly or gigantism were reviewed for musculoskeletal abnormalities. Abnormalities of peripheral joints occurred in 74% of the patients and spinal involvement in 47%, leading to significant morbidity. Joint abnormalities most frequently affected the large joints (hips, knees and shoulders) but the wrist and hand were also involved. The radiological features of acromegalic arthropathy are described, including vertical widening of the hip joint, enthesopathy and osteophytosis. A favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
10

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 28 publications
1
24
0
10
Order By: Relevance
“…In a review of 45 case notes and 20 patients with acromegaly, 22% male and 36% female patients were moderately to severely disabled by their arthropathy (8). A good response to treatment, assessed clinically and by growth hormone (GH) estimation, was associated with better employment and less severe joint disease.…”
Section: Introductionmentioning
confidence: 99%
“…In a review of 45 case notes and 20 patients with acromegaly, 22% male and 36% female patients were moderately to severely disabled by their arthropathy (8). A good response to treatment, assessed clinically and by growth hormone (GH) estimation, was associated with better employment and less severe joint disease.…”
Section: Introductionmentioning
confidence: 99%
“…UCT is the cause of disability and pain for patients and, in extreme cases, may progress to loss of function of the hand (4). In the clinical practice, sensory disturbances typically affect acromegalic patients' hands, but the majority of investigations deal with median nerve involvement (1)(2)(3)(4)(5). In particular, Jenkins et al elegantly demonstrated by magnetic resonance imaging that the predominate pathologic mechanism of median neuropathy in acromegaly seems to be edema of the perineural sheathes rather than increased volume of the carpal tunnel contents (5).…”
Section: Introductionmentioning
confidence: 99%
“…Carpal tunnel syndrome (CTS) is a common complication of acromegaly occurring in 20-64% of patients at diagnosis (1,2). Sensory disturbances in the hand of acromegalic patients may derive from a generalized nerve swelling that involves the median nerve and the ulnar nerve (3).…”
Section: Introductionmentioning
confidence: 99%
“…11,16,17 Arthralgia is seen in 70% of patients in the early period and frequently takes the form of large joint involvement. 2,8 In our study, arthralgia was present in 13 patients (34.2%).…”
Section: Discussionmentioning
confidence: 91%
“…2,3 Pain generally occurs due to the stimulating effect of GH and IGF-1 on cartilage and bone. 4 Peripheral nerve problems are also common among acromegaly patients and ensue secondary to either neural growth itself or external soft tissue/bony compression.…”
mentioning
confidence: 99%